Synchronization of chaotic systems with activity-driven time-varying interactions. (12th October 2017) - Buscarino, Arturo; Fortuna, Luigi; Frasca, Mattia; Gambuzza, Lucia Valentina; Nunnari, Giuseppe
Abstract: Interactions in many natural and man-made complex systems are not fixed but evolve in time, a crucial factor in shaping the collective behaviour of the structure. Accounting for this time dependence is approached with models based on connectivity-driven topologies, such as blinking networks and mobile agents, or activity-driven ones. While synchronization in connectivity-driven networks has been widely investigated, the phenomenon in activity-driven structures has not yet been fully explored and is here studied. We show that the onset of synchronization can be predicted when the dynamics of the link evolution is fast compared to that of the units of the network. Our results are then particularized for the case of chaotic oscillators described by the Rössler equations, where we observe that the region of synchronization is first widened and then vanishes when the switching rate decreases.